2008
DOI: 10.1007/s11240-008-9486-6
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of hairy root cultures of Maesa lanceolata and Medicago truncatula

Abstract: To study the production of secondary metabolites of Maesa lanceolata and Medicago truncatula, hairy root cultures of both plant species were established. Because maintenance of large numbers of cultures is laborious and costly, we developed a cryopreservation protocol and stored different isolated lines over time. Using encapsulation-dehydration, high survival rates were observed for both Maesa and Medicago hairy roots. Root tips were isolated and encapsulated in calcium-alginate beads, containing 0.1 M sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…For species which do not readily regenerate into plants with otherwise potentially desirable bio-containment, growth and biomass productivity features, such as petunia as identified in the current study, long-term storage solutions may be the cryopreservation of tissues in liquid N 2 (Benson and Hamill 1991;Hirata et al 2002;Lambert et al 2009). This approach does of course require a moderate-high level of expertise and technological infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…For species which do not readily regenerate into plants with otherwise potentially desirable bio-containment, growth and biomass productivity features, such as petunia as identified in the current study, long-term storage solutions may be the cryopreservation of tissues in liquid N 2 (Benson and Hamill 1991;Hirata et al 2002;Lambert et al 2009). This approach does of course require a moderate-high level of expertise and technological infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation and revival of hairy root clones of medicinal plants is a known practice (Lambert et al 2009). The survival potential of Rauwolfia hairy root cultures during and after preservation have indicted an easy adaptation to growth medium and restitution of normal growth.…”
Section: Cryopreservation Of R Serpentina Hairy Rootsmentioning
confidence: 99%
“…Hairy root cultures of numerous medicinal plants have been cryopreserved (Teoh et al 1996;Hirata et al 2002;Xue et al 2008;Lambert et al 2009). However, few studies have reported on the application of cryopreservation techniques to untransformed or adventitious root cultures (Jung et al 2001;Oh et al 2009).…”
Section: Introductionmentioning
confidence: 99%